PENDIDIKAN INKLUSI BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Mardiana; Khoiri Ahmad Khoiri (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Students with special needs who attend general elementary schools often experience difficulties in following the lessons and become schools for teachers when teaching in the absence of a companion teacher. This study aims to analyze the implementation of inclusive education for children with special needs and the management of procurement and coaching of educational personnel in primary schools. The research method uses a case study approach. Data collected through observation, interviews, and documentation. The principal, teacher / homeroom teacher as research subjects. The results obtained from the research show that: inclusive education for children with special needs in elementary schools in Melawi Regency is not according to the proper instructions, from supporting facilities, provision of accompanying teachers and coaching education staff for children with special needs (ABK). The provision of accompanying teachers and general special schools (SLB) can help children with special needs continue to attend school, therefore there needs to be concern from the central or local government, one of which is the Melawi Regency Education office so that the implementation of inclusive education can be implemented and in accordance with the procedures for implementing inclusive education for children with special needs in Melawi Regency. Keywords: inclusive education, children with special needs, companion teachers